Middle Range Theories: Application to Nursing Research - Peterson, Sandra J (Lippincott, 2004)
The most complete and detailed book devoted to middle range theories, this text examines theories and their applications in clinical nursing research and practice. The authors provide expert advice on selecting an appropriate theory for a nursing research project and on critiquing theories. The most frequently cited middle range nursing theories are explored in individual chapters. Each theory chapter includes examples of the theory’s use in research, sample application of the theory, analysis exercises, and critical thinking exercises. The Third Edition includes new chapters on Attachment theory and the Shuler Nurse Practitioner Practice Model